RESEARCH ON THE REFORM OF LANZHOU ACADEMIES IN GANSU IN THE LATE QING DYNASTY, 1840-1911 (Conferencea, 2023)
Since the middle of the 19th century, the late Qing Dynasty suffered from a formidable invasion of Western power, and national sovereignty was destroyed severely. With the deepening of social crisis, advanced Chinese actively explored the road to save the country and the people. Reform programs such as the Westernization Movement, the Hundred Days Reform, and the New Deal in the late Qing Dynasty were implemented one after another. Among them, a significant change in the field of education was that traditional educational institutions and systems were replaced by modern schools and schooling systems, which played a vital role in promoting the development of modern Chinese society. As an important city in northwest China, Lanzhou in Gansu province also experienced tremendous difference—traditional educational forms represented by academies underwent great changes.